Anthropological and transcultural nursing in the context of education for development: a historical and epistemologic perspective in the principle of the XXI century - José Siles González; Encarnación García Hernández; Luis Cibanal Juan; Roberto Galao Malo (Universidad de Alicante, 1999)
This work has the objective of clarify the development concept historically and relative it with another concept: education; and everything this process with the purpose of contributing to selection of a suitable context for educational nursing action, specially in anthropological and transcultural nursing.